Analiza jakosti možnih sečenj z vidika uvajanja sodobnih tehnologij gozdnega dela na severnem predelu Slovenije - Krč, Janez (Gozdarski vestnik, 2004)
The article presents an analysis of the suitability of Slovenia's northern firests as to the application of mechanized cutting. The areas have been chosen because of the specific stabd conditions, i.e. predominantly conifer stands in comperison to other parts of Slovenia. Previus research has shown that conifer stands are much more suitable for mechanized forestry work. The issue of concentration of work is treated separately, in connection to the intensity of allowable cuts by analysed areas has been made. Higher concentration values are more suitable for mechanized work, since along with the increase of the concetrations the productive time also increases, which has the strongest influence on the profitability of the work. Differences in the concentration values of allowable harvesting on areas suitable for mechanized cutting have been noted both among the chosen areas as also among different ownership section. The criteria for selection of the areas were: terrain slope, share of conifers in the growing stock of the stands and microrelief characteristics (sinkholes).
Keywords: severna Slovenija; strojna sečnja